Analisis Pengaruh Religiosity dan Ethical Judgements terhadap Tax Avoidance - Saksono, Lalang; Sandag, Eltie Christi; Affandi, Muhammad Rispan; Patiran, Andarias; Marani, Yohanes (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The purpose of this study is to analyze Religiosity and Ethical Judgments on Tax Avoidance. This study used a survey of Corporate Taxpayers in Purwokerto City. Corporate Taxpayers were chosen because, in terms of total Indonesian state revenue, corporate taxpayers contribute more than individual taxpayers. Hypothesis testing used regression analysis with the help of the SmartPLS 4.0.9.9 program. The results showed that Religiosity and Ethical Judgments have a positive and significant effect on tax avoidance.